A new method for determining water adsorption phenomena on metal surfaces in a vacuum - Sefa, Makfir (Materiali in tehnologije, 2014)
A new method for measuring the amount of adsorbed water vapor on different technical metal surfaces in vacuum systems after exposure to water vapor has been developed. The method is based on a measurement of the pressure - time response after the sudden introduction of a constant gas flow into the vacuum chamber. For non-adsorbing gases the pressure approaches the equilibrium value with a time constant t that is equal to t = V/S, where V is the volume of the system and S is the effective pumping speed for a given gas. For adsorbing a gas like water vapor the approach of the pressure to the equilibrium value is delayed due to the adsorption of molecules on the surfaces of the vacuum system. The method was evaluated using aluminum foils with different surface areas. The measured data were modeled using the Langmuir, Freundlich and Temkin isotherms. The measured water coverage on the stainless-steel and aluminum surfaces was less than one monolayer for pressures ranging from 8 x 10-5 mbar to 1 x 10-2 mbar. The best fit to the measured coverage was obtained when using the Freundlich isotherm.
Keywords: vodna para; water vapor; adsorpcija; adsorption; pokritje površine; surface coverage; adsorption isotherm; adsorpcijska izoterma